(untitled) (Indonesian Journal of Primatology, 2025)
Siamang (Symphalangus syndactylus) is one of the endemic Sumatran primate from Hylobatidae family. Siamang distribution can be found on North Sumatra, southern Lake Toba to Bukit Barisan Selatan. Siamang has a unique morphology in the form of voice bag (gular sac) so it can make a very loud sound in voicing behavior. The purpose of this study was to identified the distribution, population characteristic and the voice timing of siamang in KHDTK Aek Nauli. There are 15 distiribution points of siamang that dispersed in three types of land cover, it is primary and secondary as well as pine dominated forests. Based on Chi-square test was obtained that spatial pattern of siamang have been clumped, whichmeans x2hit more than or equal to x20,025. The number of siamang group are identified about 15 groups with 49 individuals. The population was estimated between 39±11 individuals with accuracy of 71.8%. Population density was around2.05±0.57 individuals/km2 and 0.78±0.57 groups/km2. The voice timing of siamang in KHDTK Aek Nauli is most often done at 09.00–11.00 a.m.